Erosive Potential of Cola-Type Soft Drinks on the Surface of Restorative Materials: In Vitro Study - Marília Gabriela Corrêa Momesso; Kelly Maria Silva Moreira; Renata Cristiane da Silva; Júlia Vitório Octaviani; José Carlos Pettorossi Imparato (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2025)
Objective: To evaluate the Knoop hardness of two types of glass ionomer cement - VitroMolar (VM) and Riva Self Cure (RSC), as well as the composite resin Z350 (CR), when exposed to two Cola-type soft drinks. Materials and Methods: Forty specimens were prepared using a matrix. After placing a polyester strip, the materials were manipulated according to the manufacturers' guidelines. They were kept in an environment with a relative humidity of approximately 100% and an ambient temperature of approximately 23ºC. After 24 hours, the polyester strips were removed from the matrix. The specimens received no protective layer or underwent surface finishing and polishing, and their surface hardness was evaluated. ANOVA with repeated measures was performed, followed by Tukey's test and a t-test. Results: Regarding the erosive potential of the drinks for each material, cola-type soft drinks (Coke Regular and Coke Zero) caused a significant variation in hardness for VM and the CR (p<0.05). As for RSC, only Coca-Cola Zero reduced the hardness of the material (p<0.05). Conclusion: Despite the composite resin exhibiting superior initial and final hardness, the material presented the most significant variation in hardness when compared to glass ionomer cement, regardless of the beverage used.